Characteristics of nanoclay and calcined nanoclay-cement nanomatrices by combination of QXDA and TGA techniques - Hakamy, Ahmad Magbul M; Shaikh, Faiz; Low, It Meng (Institute of Research and Journals, 2015)
The influence of nanoclay (NC) and calcined nanoclay (CNC) on the mechanical and thermal properties of cement nano-matrices presented. Calcined nanoclay is prepared by heating nanoclay (Cloisite 30B) at 900° C for 2h. Estimation of Ca(OH)2 content in the cement nanomatrix is studied by the combination of Quantitative X-ray Diffraction Analysis (QXDA) and thermogravimetry analysis (TGA) techniques. Results showed that the microstructure and compressive strength of the cement nano-matrices are improved as a result of NC and CNC addition. An optimum replacement of ordinary Portland cement with 1 wt% CNC is observed through decreased the porosity and increased compressive strength of cement nano-matrices. Cost-benefit analysis indicates that nanoparticles are expensive but from economic point of view nanoclay is used in very small amount (i.e. 1 wt. %) in cementitious materials. As a result nanoclay does not add any significant cost but improves the mechanical properties significantly.